Pemanfaatan Media Berbasis Artificial Intelligence Dalam Pendidikan Agama Islam Tinjauan Sistematis Terhadap Implementasi, Etika, Dan Tantangan Pedagogis - Jessica Tri Agustin; Nurlaili; Dayun Riadi (Yayasan Madinah Al-Aziziyah, 2026)
The development of artificial intelligence (AI) has brought significant transformations in the global educational landscape, including Islamic Religious Education (PAI). This article aims to systematically examine the implementation, ethical considerations, and pedagogical challenges in utilizing AI-based media in Islamic Religious Education (PAI) learning. This research uses the Systematic Literature Review (SLR) method with the PRISMA flow, collecting and synthesizing the latest academic literature from indexed databases through thematic analysis. The findings indicate that AI media has the potential to improve learning personalization, tajwid pronunciation accuracy, and Quran memorization retention through adaptive systems and real-time feedback. However, the integration of AI also raises ethical dilemmas related to scientific validity (“digital sanad”), the risk of algorithmic hallucinations, data privacy, and the shift in the teacher's role from murabbi to technical facilitator. Pedagogically, the main challenge lies in preserving the tazkiyatun nafs dimension and the formation of morals that inherently cannot be replicated by machines. It is concluded that the use of AI in Islamic Religious Education (PAI) must be based on an Islamic ethical framework (maqashid sharia and the principle of tabayyun), with AI positioned as a co-pedagogue that complements, not replaces, the central role of teachers in guiding students' spirituality and character. Strategic recommendations include developing ethical guardrails, improving the digital literacy of educators, and designing media that is transparent and has verified scientific sources.